Vitamin D status and asthma, lung function, and hospitalization among British adults - Zhu, Yiqun; Jing, Danrong; Liang, Huaying; Li, Dianwu; Chang, Qinyu; Shen, Minxue; Pan, Pinhua; Liu, Hong; Zhang, Yan (Frontiers in Nutrition, 2022)
Background Amount of attention was received by vitamin D in asthma due to ever-increasing reports of association between vitamin D and asthma with inconsistent results. Objective To investigate the role of serum vitamin D in asthma prevalence, lung function and asthma control in adults. Methods Multivariable logistic regression was applied to assess the relationship between serum vitamin D and asthma prevalence, lung function (FEV1, FVC and FEV1 /FVC), current wheeze and asthma linked hospitalizations in a cross-sectional study of 435,040 adults aged 37 to 73 years old from the UK Biobank. Results Compared to vitamin D deficiency, the odds of asthma were decreased by 6.4% (aOR=0.936; 95% CI: 0.911 to 0.962; P<0.001) and 9.8% (aOR=0. 0.902; 95% CI: 0.877 to 0. 0.927; P<0.001) in individuals with insufficient and optimal vitamin D concentration, respectively, in the fully adjusted model. In total asthmatic patients, serum vitamin D was obviously and positively related with FEV 1 (b=1.328 mL, 95%CI=0.575-2.080), FVC (b=2.018mL, 95%CI=1.127-2.908) and FEV1 /FVC (b=0.006%, 95%CI=0.002-0.010). Asthmatic patients whose vitamin D level was in the deficient category had 9.3%-19.9% higher odds of current wheeze than insufficient categories (aOR=0.907; 95% CI: 0.861 to 0.957; P<0.001) and optimal categories (aOR=0.801; 95% CI: 0.759 to 0.845; P<0.001), but the relationship between vitamin D and asthma hospitalization was not significant. Conclusion Vitamin D deficiency was related with higher odds of asthma and current wheeze, and lower lung function in a large sample size study of British adults. Our results indicate a potential positive impact of serum vitamin D on asthma occurrence and disease control in adults.